A first insight into the estimation of uncertainty associated with storage and physical preparation of forest moss samples for trace element analysis. (February 2020) - Dołęgowska, Sabina; Migaszewski, Zdzisław M.
Abstract: To assess the level of uncertainty related to storage and physical preparation, 27 combined samples of moss species Pleurozium schreberi (Brid.) Mitt and their duplicates were collected within three forest areas. Each sample was divided into three sub-samples subjected to further treatment: D – drying (20–25 °C), F – freezing (−20 °C), and A – acclimatization (4 °C). After 7 days, all the samples were split into two sub-samples for physical preparation, dry (P1) and wet (P2) cleaning, respectively. Subsequently, the samples were milled, digested in a closed microwave system and analysed for Cd, Co, Cu, Fe, Mn, Ni, Pb and Zn using the flame (FAAS) and graphite furnace (GFAAS) atomic absorption spectrometry. In four out of eight metals (Cu, Fe, Mn, Ni), the lowest mean values were in the samples stored at −20 °C, however, in two cases (Cd, Pb), the acclimatization procedure also led to lower concentrations. Except for Mn and Zn, the higher contents of elements were found in samples that were dry cleaned after storage. The level of sample storage uncertainty ( s r stor ) varied from 4.8% to 24.0%. The uncertainty related to preparation was in the range of 3.0–21.0%. Only for Co, the contribution of s r stor uncertainty to the budget of uncertainty was lower than that from physical preparation. For the other elements, this contribution was at a similar level (Ni, Zn) or higher (Cd, Cu, Fe, Mn, Pb). In most cases, the lower s r prep values were obtained when the samples were dry cleaned after storage, regardless of the storage conditions. Highlights: Moss samples were stored under three different conditions. After storage samples were cleaned using dry and wet techniques. Higher contents of elements were found in samples dry cleaned after storage. The level of sample storage uncertainty varied from 4.8% to 24.0%. Uncertainty related to preparation was in the range of 3.0–21.0%.